Exosomal lncRNA HOTAIR promotes osteoclast differentiation by targeting TGF‐β/PTHrP/RANKL pathway. Issue 3 (3rd January 2023) - Zhang, Chengcheng; Yang, Jiyong; Zhu, Zhiyao; Qin, Jingru; Yang, Lu; Zhao, Xiaoxue; Su, Wan; Cai, Yuejiao; Yang, Jia; Wang, Fengying; Chen, Wenlian; Gu, Honggang; et al.
Abstract: Bone tissue is a common metastatic site of lung cancer, and bone metastasis is characterized by abnormal differentiation and malfunction of osteoclast, and the roles of exosomes derived from lung cancer have attracted much attention. In our study, we found that the level of HOTAIR expression in A549 and H1299 exosomes was higher than those of normal lung fibrocytes. Overexpression of HOTAIR in A549 and H1299 exosomes promoted osteoclast differentiation. Furthermore, A549‐Exos and H1299‐Exos targeted bone tissues, and bone formation was significantly inhibited in vivo. Mechanistically, exosomal lncRNA HOTAIR promoted bone resorption by targeting TGF‐β/PTHrP/RANKL pathway.